Implementasi Dan Dampak Suatu Kebijakan Pemerintah Dalam Penanggulangan Tingkatnya Pengangguran Di Kota Batam (Studi : Penyelesaian Perselisihan Hubungan Industrial) - Wulandari, Ayu; Dompak, Timbul; Khairina, Etika (Prosiding, 2024)
Based on the article, it has been analyzed according to the results obtained from the journal on a problem that occurs in the implementation and impact on a government policy on the city of Batam. With the taking of a problem in Batam City, in order to immediately illustrate / think of what has happened to government policies in Batam City. Policy is a series or principle concept in which guidelines and plans for work can be implemented based on action or leadership. Based on the above policy, it can be exemplified against the title to be analyzed, namely the implementation and impact of government policies in overcoming the level of unemployment in Batam City. By determining this analysis so that a goal can be achieved. So from this analysis it is very interesting to discuss, because of these problems that have occurred in the city of Batam and from the Batam city government and Dipnaker are still confused to find a solution. In an impact of the implementation of this public policy, which is related to the unemployment rate in Batam City, there are many losses that occur to the community. Which is where people always complain to the Batam City Government regarding the difficulty of finding a job. So that a government policy has not been running as optimally as possible, because there are many obstacles to the local community that are needed on various indicators in the implementation process so that a goal is to make Batam City prosperous and can be implemented optimally and will not cause various debates between the community and the government.